(untitled) - Phillips, Deborah (Longman, 2001)
Focusing on skill-building practice for more advanced students, this complete, multimedia TOEFL(R) course now helps students prepare for both the paper and computer versions of the TOEFL(R) Test. Longman Complete Course for the TOEFL(R) Test is appropriate for use as a primary test preparation text, as a supplement to general course, or as a self-study aid. The Complete Course is accompanied by a set of audiocassettes or dual-platform CDs and a User's Guide. The audiocassettes and CDs contain recorded listening material from the book. The User's Guide contains scripts of the listening material and an answer key with explanations. Coming soon...a Bonus Test Disk with an additional bank of questions.
Keywords: English language,Test of english as a foreign language; Texbooks for foreign speakers,Study guides